Endurance Tests Ability to predict Chronicity in First Episode Acute Low Back Pain Patients - Ali Asghar Norasteh; Esmaeil Ebrahimi-Takamjani; Mahyar Salavati (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Despite evaluation of spinal muscle endurance was done in chronic low back pain, this has not been studied in first episode acute low back pain. The purpose of present study was comparatively evaluating patients with first-episode low back pain and healthy subjects to predict disability and chronicity after six weeks with spinal muscle endurance tests. Materials & Methods: Through an analytical, cross sectional and case - control study in the first stage of research Eliot's spinal endurance tests were used to evaluate endurance. Disability and pain were used to assess recovery. The study was conducted in two groups of patients (n=32) and normal subjects (n=51) using non-randomized simple sampling. In the second stage, a longitudinal prospective study was done. Studied variables were compared in recovered and non recovered patients after six weeks. Data were analyzed by using Kolmogorof - Smirnoff test, independent T test and Chi-Square. Results: The results of independent t tests showed lower muscular endurance in patients compared to normal individuals (P<0.0001). Also the results of independent t-tests showed lower flexor endurance in unrecovered patients (P<0.04). Conclusion: It seems low back pain patients can contract decreased endurance in the first episode and no need to repeat episodes. Results show may be endurance tests could differentiate acute low back pain patients with high risk to chronicity and disability.